2024
DOI: 10.1111/jmwh.13606
|View full text |Cite
|
Sign up to set email alerts
|

Prescriptive Authority for Direct Entry Midwives in Washington State: Increasing Client Access to Contraception

Britney Zell,
Kristin Effland,
Mercedes Snyder
et al.

Abstract: Improving health and achieving health equity includes access to sexual and reproductive health care for all populations, especially those most in need. However, access to life‐saving and life‐affirming contraception with an individual's chosen perinatal provider can be impeded by restrictive regulations that limit scope and practice authority. This is especially true for the majority of community and direct entry midwives in the United States who have historically been unable to legally provide effective contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…10,11 Meanwhile, in the United States, midwives in Washington state recently (2022) gained prescriptive authority to prescribe contraception. 12 Some studies have reported positive experiences with postpartum contraceptive care provided by midwives. These experiences were characterised by convenience, trust, comfort, and the extensive knowledge of midwives.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Meanwhile, in the United States, midwives in Washington state recently (2022) gained prescriptive authority to prescribe contraception. 12 Some studies have reported positive experiences with postpartum contraceptive care provided by midwives. These experiences were characterised by convenience, trust, comfort, and the extensive knowledge of midwives.…”
Section: Introductionmentioning
confidence: 99%